Health Services as Credence Goods: a Field Experiment. Issue 629 (28th February 2020) - Gottschalk, Felix; Mimra, Wanda; Waibel, Christian
Abstract: Agency problems are a defining characteristic of healthcare markets. We present the results from a field experiment in the market for dental care: a test patient who does not need treatment is sent to 180 dentists to receive treatment recommendations. In the experiment, we vary the socio-economic status of the patient and whether a second opinion signal is sent. Furthermore, measures of market, practice and dentist characteristics are collected. We observe an overtreatment recommendation rate of 28% and a striking heterogeneity in treatment recommendations. Furthermore, we find significantly fewer overtreatment recommendations for patients with higher socio-economic status compared with lower socio-economic status for standard visits, suggesting a complex role for patients' socio-economic status. Competition intensity, measured by dentist density, does not have a significant influence on overtreatment. Dentists with shorter waiting times are more likely to propose unnecessary treatment.